Yizong Tongluo formula attenuates idiopathic pulmonary fibrosis and inflammatory injury by inhibiting HIF-1α/LSH/SCD1-mediated ferroptosis - Ma, Xin; Wang, Xin; Jiang, Daobin; Tuerxun, Yiminnuer; Tao, Siming; Li, Fengsen; Wei, Yanrong; Yang, Liu; Xi, Lei; Wang, Ling (Frontiers in Immunology, 2026)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive disease characterized by chronic inflammation, aberrant tissue remodeling, and hypoxia. In traditional Chinese medicine (TCM), it is classified as Qi deficiency–blood stasis syndrome. The mechanism of Yizong Tongluo Formula (YZTLF), a Traditional Chinese Medicine (TCM) herbal formulation and effective pharmaceutical agent for the clinical treatment of IPF, remains unclear.MethodsThis study investigated the immunomodulatory and anti-fibrotic mechanisms of YZTLF for this IPF subtype by focusing on the HIF-1α/LSH/SCD1 signaling pathway and ferroptosis-induced inflammatory injury. We began by analyzing clinical samples from IPF patients with Qi deficiency and blood stasis was conducted to assess the signalling axis and ferroptosis markers. Molecular and histological analyzes were performed using TGF-β-treated MRC-5 fibroblast cells and a bleomycin-induced rat model of pulmonary fibrosis.ResultsClinical analysis revealed a dysregulation of the HIF-1α/LSH/SCD1 axis and altered levels of ferroptosis markers in patients. In vitro, YZTLF significantly downregulated HIF-1α and LSH expression while upregulating SCD1 (p < 0.01). Importantly, the treatment markedly suppressed ferroptosis, as evidenced by reduced intracellular Fe2+ and ACSL4 levels alongside increased Glutathione Peroxidase 4 (GPX4) and GSH expression (p < 0.01). It also inhibited TGF-β-induced fibroblast activation, significantly decreasing α-SMA and Collagen I protein levels (p < 0.01). In vivo, the YZTLF treatment attenuated bleomycin-induced lung injury, reduced inflammatory cell infiltration, preserved alveolar architecture, and reduced collagen deposition, alongside normalizing of HIF-1α/LSH/SCD1 signaling and restoration of antioxidant levels.ConclusionThese findings indicate that YZTLF mitigates IPF progression in the context of Qi deficiency and blood stasis by suppressing ferroptosis-driven inflammation and remodeling the hypoxic microenvironment via the HIF-1α/LSH/SCD1 pathway. This provides a mechanism-based rationale for its use in this TCM-defined IPF subtype.